High-entropy ceramic powder as well as preparation method and application thereof

By dissolving the metal source in n-propanol, adding acetylacetone and other sources, high-entropy ceramic powder is prepared after curing and heat treatment, the problem of insufficient density and purity of high-entropy boronide ceramics in the prior art is solved. , high-purity and low oxygen content of high entropy ceramic powder preparation is achieved.

CN119462163APending Publication Date: 2025-02-18GUANGZHOU UNIVERSITY

Patent Information

Application Number
CN202410787755.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to obtain high-density, high-purity high-entropy boric ceramics through conventional sintering methods, and have low density and contain oxide impurities.

Method used

A high-entropy ceramic powder is prepared by dissolving the metal source in n-propanol, adding acetylacetone to form a polymer solution, and then adding carbon and boron sources in turn.

Benefits of technology

On the premise of reducing the preparation temperature, the element uniformity of high-entropy ceramic powder is significantly improved, the oxygen content is reduced, and the product purity is improved, and the oxygen content is as low as 0.65%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462163A_ABST
    Figure CN119462163A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high-entropy compound preparation, in particular to high-entropy ceramic powder and a preparation method and application thereof.The preparation method comprises the following steps that a metal source is dissolved in n-propyl alcohol and mixed to be uniform, and an n-propyl alcohol solution of the metal source is obtained; adding acetylacetone into the n-propyl alcohol solution of the metal source, and uniformly mixing to obtain a polymer solution of the metal source; sequentially adding a carbon source and a boron source into the polymer solution of the metal source, and uniformly mixing to obtain a precursor solution; sequentially carrying out curing and heat treatment on the precursor solution to obtain high-entropy ceramic powder; wherein the molecular formula of the high-entropy ceramic powder is MB2, and M is four metal elements of Ta, Nb, Zr and Ti. According to the preparation method, the uniformity of each element on the molecular scale can be greatly improved, so that the oxygen content of the high-entropy ceramic powder is reduced on the premise of reducing the preparation temperature, and the purity of the product is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high entropy compound preparation, and in particular to a high entropy ceramic powder and a preparation method and application thereof. Background Art

[0002] High entropy compounds are a type of inorganic non-metallic materials formed by the solid solution of multiple components (generally greater than or equal to 5) in equal or nearly equal proportions, including high entropy oxides, nitrides, carbides, borides, etc. In 2015, Maria from North Carolina State University and Curtarolo et al. from Duke University synthesized a rock salt structured (MgNiCoCuZn)O ceramic for the first time, opening the prelude to the research of high entropy ceramics.

[0003] At present, the research on high entropy boride ceramics is mainly focused on diborides (MB2) of transition metal IVB and VB groups. Most of these borides have an AlB2-type hexagonal structure, that is, the B atoms form a layered structure similar to graphite, and metal atoms are interspersed between the layers. It is precisely because of the strong covalent characteristics of the BB ring and the MB bond that MB2 has a very high melting point, hardness, strength, thermal stability and conductivity, and can therefore be used in aerospace, energy and other fields.

[0004] High-entropy boride ceramics have ultra-high melting points and strong covalent bond characteristics, and the raw material powder also contains many impurities, so it is difficult to obtain high-density boride ceramics through conventional sintering methods. To obtain high-density and high-purity high-entropy boride ceramics, it is first necessary to obtain high-quality powder.

[0005] Currently, the main preparation methods for high-entropy ceramic powders include mechanical alloying, direct synthesis, carbon / boron thermal reduction, etc. However, the high-entropy ceramics prepared by the above methods have low density and contain oxide impurities. How to obtain high-entropy boride powders with high composition uniformity and high purity is the current technical bottleneck problem.

[0006] For example, Luo Jian's team (High-Entropy Metal Diborides: A New Class of High-Entropy Materials and a New Type of Ultrahigh Temperature Ceramics, Scientific Reports, 2016, 6: 37946) directly subjected five types of boride commercial powders to high-energy ball milling and then spark plasma sintering. The relative density of the resulting samples was very low, ranging from 92% to 93%, and there were also some oxide impurity phases, which greatly reduced the various properties of boride ceramics. Guo Weimin et al. from Guangdong University of Technology (Dense high-entropy boride ceramics with ultra-high hardness, Scripta Materialia, 2019, 164: 135-139) used metal oxides and amorphous boron powder as raw materials and synthesized submicron-sized (TiO2) by boron thermal reduction at 1600°C. 0.2 Cr 0.2 Zr 0.2 Hf 0.2 Ta 0.2 )B2 and other powders, and then sintered them, but oxide impurities were present in the final ceramic sample. At the same time, they used carbon / boron thermal reduction method to prepare (Ti 0.2 Zr 0.2 Nb 0.2 Hf 0.2 Ta 0.2 )B2 and other powders, and then dense bulk ceramics were prepared by spark plasma sintering, but oxide impurities still existed in them.

[0007] In view of this, the present invention is proposed. Summary of the invention

[0008] The object of the present invention is to provide a high entropy ceramic powder and a preparation method thereof, which can greatly improve the uniformity of each element at the molecular scale, thereby reducing the oxygen content of the high entropy ceramic powder and improving the purity of the product under the premise of lowering the preparation temperature.

[0009] In a first aspect, the present invention provides a method for preparing a high entropy ceramic powder, comprising the following steps:

[0010] S1, dissolving the metal source in n-propanol, mixing evenly, to obtain an n-propanol solution of the metal source;

[0011] S2, adding acetylacetone to the n-propanol solution of the metal source, mixing evenly, to obtain a polymer solution of the metal source;

[0012] S3, sequentially adding a carbon source and a boron source to the polymer solution of the metal source, mixing them evenly, to obtain a precursor solution;

[0013] S4, the precursor solution is solidified and heat-treated in sequence to obtain a high entropy ceramic powder;

[0014] Among them, the molecular formula of the high entropy ceramic powder is MB2, wherein M is four metal elements of Ta, Nb, Zr and Ti.

[0015] In the preparation method of high entropy ceramic powder of the present invention, four metal elements of Ta, Nb, Zr and Ti are first selected to prepare high entropy ceramic powder, and raw materials Ta source, Nb source, Zr source and Ti source are dissolved in n-propanol. Compared with other alcohols, n-propanol can not only fully ensure the full dissolution of the metal source, but also is not easy to volatilize and has a relatively low melting point, which can reduce the energy consumption of the preparation process. Therefore, n-propanol is selected as the solvent of the metal source to obtain a better uniformity than the traditional mixing method; acetylacetone is further added to make the n-propanol solution of the metal source form a polymer solution of multiple transition metal sources, and can effectively prevent monomer self-polymerization and liquid segregation; then a carbon source and a boron source are added in sequence to prepare a precursor solution with higher purity, and the precursor solution is successively cured and heat treated to prepare the high entropy ceramic powder.

[0016] Therefore, the preparation method can greatly improve the uniformity of each element at the molecular scale, thereby reducing the oxygen content of the high entropy ceramic powder and improving the purity of the product under the premise of reducing the preparation temperature. Studies have shown that the oxygen content of the high entropy ceramic powder prepared by the present invention is as low as 0.65%, which has the advantages of high purity and low oxygen content.

[0017] As a preferred embodiment of the present invention, the Ta source is TaCl5, the Nb source is NbCl5, and the Zr source is ZrCl4, C 12 H 28 O4Zr or ZrOCl2·8H2O, Ti source is TiCl4, C 16 H 36 O4Ti or C8H 20 Any one of O4Ti, and the molar ratio of the four metal elements of Ta source, Nb source, Zr source and Ti source is 1:1:1:1.

[0018] As a preferred embodiment of the present technical solution, the carbon source is preferably phenolic resin. Phenolic resin has a high residual carbon rate during thermal decomposition, which can ensure the excess carbon source required in the process of forming high entropy boride and avoid the problem of inability to synthesize due to insufficient carbon source.

[0019] As a preferred embodiment of the present technical solution, the boron source is tetrahydroxydiborane. One mole of tetrahydroxydiborane can provide two B atoms, which is easier to form a network structure than using boric acid.

[0020] As a preferred embodiment of the present technical solution, the total molar number of the acetylacetone and all the metal elements is equal, so that the acetylacetone and all the metal elements form a uniform and stable polymer solution.

[0021] As a preferred embodiment of the present technical solution, the total molar ratio of the boron source to all metal elements is (1-5):1, and preferably 2.5:1. Under this ratio, tetrahydroxydiborane and metal alkoxide are hydrolyzed and polycondensed. At the same time, tetrahydroxydiborane is a hydroxy compound and can undergo ester exchange with acetylacetone to obtain a precursor.

[0022] As a preferred embodiment of the present technical solution, during the curing, the precursor solution is placed at 80-200° C. for full curing, and after curing, it is ground and pulverized to obtain the precursor powder.

[0023] As a preferred embodiment of the present technical solution, during the heat treatment, the temperature is raised to 1500-2200°C at a heating rate of 3-9°C / min, and then maintained at 1500-2200°C for 0.5-2h, and then cooled to room temperature to obtain high entropy ceramic powder, wherein the atmosphere of the heat treatment is preferably a protective atmosphere such as argon.

[0024] In the second aspect, the present invention also provides a high entropy ceramic powder prepared by the above-mentioned preparation method, which should also belong to the protection scope of the present invention. The molecular formula of the high entropy ceramic powder is (Ta 0.25 Nb 0.25 Zr 0.25 Ti 0.25 )B2.

[0025] In a third aspect, the present invention also discloses the application of the above-mentioned high entropy ceramic powder, specifically referring to the application of high entropy ceramic powder in the fields of aerospace or energy.

[0026] The high entropy ceramic powder (Ta 0.25 Nb 0.25 Zr 0.25 Ti 0.25 )B2 has excellent melting point, hardness, strength, thermal stability and conductivity, so it can be used in aerospace, energy and other fields.

[0027] The method for preparing high entropy ceramic powder of the present invention has at least the following beneficial effects:

[0028] 1. In the preparation method of the high entropy ceramic powder of the present invention, the raw materials Ta source, Nb source, Zr source, and Ti source are first dissolved in n-propanol, thereby obtaining a better uniformity than the traditional mixing method; acetylacetone is further added to make the n-propanol solution of the metal source form a polymer solution of the metal source to prevent the segregation of the liquid; then the carbon source and the boron source are added in sequence to prepare a precursor solution with a higher purity, and the precursor solution is cured and heat-treated in sequence to prepare the high entropy ceramic powder. Therefore, this preparation method can greatly improve the uniformity of each element at the molecular scale, thereby reducing the oxygen content of the high entropy ceramic powder and improving the purity of the product under the premise of lowering the preparation temperature. Studies have shown that the high entropy ceramic powder prepared by the present invention has an oxygen content as low as 0.65%, which has the advantages of high purity and low oxygen content;

[0029] 2. The method for preparing high entropy ceramic powder of the present invention requires simple equipment, readily available raw materials, low energy consumption, and is easy to promote on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 The present invention is obtained after heat treatment at 1500°C (Ta 0.25 Nb 0.25 Zr 0.25 Ti 0.25 ) XRD pattern of B2 high entropy ceramic powder;

[0032] Figure 2 The present invention is obtained after heat treatment at 1600°C (Ta 0.25 Nb 0.25 Zr 0.25 Ti 0.25 ) XRD pattern of B2 high entropy ceramic powder;

[0033] Figure 3 The present invention is obtained after heat treatment at 1700°C (Ta 0.25 Nb 0.25 Zr 0.25 Ti 0.25 ) XRD pattern of B2 high entropy ceramic powder;

[0034] Figure 4 The present invention is obtained after heat treatment at 1800°C (Ta 0.25 Nb 0.25 Zr 0.25Ti 0.25 ) XRD pattern of B2 high entropy ceramic powder;

[0035] Figure 5 The present invention is obtained after heat treatment at 2000℃ (Ta 0.25 Nb 0.25 Zr 0.25 Ti 0.25 ) XRD pattern of B2 high entropy ceramic powder;

[0036] Figure 6 The present invention is obtained after heat treatment at 2200°C (Ta 0.25 Nb 0.25 Zr 0.25 Ti 0.25 )XRD pattern of B2 high entropy ceramic powder. DETAILED DESCRIPTION

[0037] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0038] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0039] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Example 1

[0041] S1, weigh 0.01mol TaCl5, 0.01mol NbCl5, 0.01mol C 12 H 28 O4Zr, 0.01mol C 16 H 36 O4Ti is dissolved in a n-propanol solution to obtain a n-propanol solution of a metal source;

[0042] S2, adding 0.04 mol of acetylacetone solution to the n-propanol solution of the metal source, stirring evenly, to obtain a polymer solution of the metal source;

[0043] S3, adding 0.015 mol of phenolic resin to the polymer solution of the metal source, stirring evenly, and then adding 0.16 mol of tetrahydroxydiborane, stirring evenly, to obtain a precursor solution;

[0044] S4, the precursor solution was solidified at 100 ° C, and after grinding, the precursor powder was obtained. The precursor powder was heated to 1500 ° C at a rate of 5 ° C / min, and then kept at 1500 ° C for 1 h. The protective atmosphere was argon gas. After cooling to room temperature, (Ta 0.25 Nb 0.25 Zr 0.25 Ti 0.25 )B2 high entropy ceramic powder, its XRD spectrum is attached Figure 1 .

[0045] Depend on Figure 1 It can be seen that the (Ta 0.25 Nb 0.25 Zr 0.25 Ti 0.25 ) The diffraction peak of B2 high entropy ceramic powder is relatively sharp, indicating that a solid solution has been formed, which means that the high entropy ceramic powder has been successfully prepared.

[0046] Example 2

[0047] S1, weigh 0.015mol TaCl5, 0.015mol NbCl5, 0.015mol C 12 H 28 O4Zr, 0.015molC 16 H 36 O4Ti is dissolved in a n-propanol solution to obtain a n-propanol solution of a metal source;

[0048] S2, adding 0.06 mol of acetylacetone solution to the n-propanol solution of the metal source, stirring evenly, to obtain a polymer solution of the metal source;

[0049] S3, adding 0.015 mol of phenolic resin to the polymer solution of the metal source, stirring evenly, and then adding 0.3 mol of tetrahydroxydiborane, stirring evenly, to obtain a precursor solution;

[0050] S4, the precursor solution was solidified at 120°C, and after grinding, the precursor powder was obtained. The precursor powder was heated to 1600°C at a heating rate of 6°C / min, and then kept at 1600°C for 1.5h, with argon as the protective atmosphere. After cooling to room temperature, (Ta 0.25 Nb 0.25 Zr 0.25 Ti 0.25)B2 high entropy ceramic powder, its XRD spectrum is attached Figure 2 .

[0051] Depend on Figure 2 It can be seen that the (Ta 0.25 Nb 0.25 Zr 0.25 Ti 0.25 ) The diffraction peak of B2 high entropy ceramic powder is relatively sharp, indicating that a solid solution has been formed, which means that the high entropy ceramic powder has been successfully prepared.

[0052] Example 3

[0053] S1, weigh 0.015mol TaCl5, 0.015mol NbCl5, 0.015mol C 12 H 28 O4Zr, 0.015molC 16 H 36 O4Ti is dissolved in a n-propanol solution to obtain a n-propanol solution of a metal source;

[0054] S2, adding 0.06 mol of acetylacetone solution to the n-propanol solution of the metal source, stirring evenly, to obtain a polymer solution of the metal source;

[0055] S3, adding 0.02 mol of phenolic resin to the polymer solution of the metal source, stirring evenly, and then adding 0.36 mol of tetrahydroxydiborane, stirring evenly, to obtain a precursor solution;

[0056] S4, the precursor solution was solidified at a temperature of 150°C, and after grinding, a precursor powder was obtained; the precursor powder was heated to 1700°C at a heating rate of 6°C / min, and then kept at 1700°C for 2h, with an argon atmosphere as the protective atmosphere, and cooled to room temperature to obtain (Ta 0.25 Nb 0.25 Zr 0.25 Ti 0.25 )B2 high entropy boride ceramic powder, its XRD spectrum is shown in the attached Figure 3 .

[0057] Depend on Figure 3 It can be seen that the (Ta 0.25 Nb 0.25 Zr 0.25 Ti 0.25 ) The diffraction peak of B2 high entropy ceramic powder is relatively sharp, indicating that a solid solution has been formed, which means that the high entropy ceramic powder has been successfully prepared.

[0058] Example 4

[0059] S1, weigh 0.02mol TaCl5, 0.02mol NbCl5, 0.02mol C 12 H 28 O4Zr, 0.02mol C 16 H 36 O4Ti is dissolved in a n-propanol solution to obtain a n-propanol solution of a metal source;

[0060] S2, adding 0.08 mol of acetylacetone solution to the n-propanol solution of the metal source, stirring evenly, to obtain a polymer solution of the metal source;

[0061] S3, adding 0.025 mol of phenolic resin to the polymer solution of the metal source, stirring evenly, and then adding 0.32 mol of tetrahydroxydiborane, stirring evenly, to obtain a precursor solution;

[0062] S4, the precursor solution was solidified at a temperature of 140°C, and after grinding, a precursor powder was obtained; the precursor powder was heated to 1800°C at a heating rate of 5°C / min, and then kept at 1800°C for 1.5h, the protective atmosphere was argon, and after cooling to room temperature, (Ta 0.25 Nb 0.25 Zr 0.25 Ti 0.25 )B2 high entropy ceramic powder, its XRD spectrum is attached Figure 4 .

[0063] Depend on Figure 4 It can be seen that the (Ta 0.25 Nb 0.25 Zr 0.25 Ti 0.25 )The diffraction peak of B2 high entropy ceramic powder is sharp and strong, indicating that the degree of solid solution formation is better.

[0064] Example 5

[0065] S1, weigh 0.01mol TaCl5, 0.01mol NbCl5, 0.01mol C 12 H 28 O4Zr, 0.01mol C 16 H 36 O4Ti is dissolved in a n-propanol solution to obtain a n-propanol solution of a metal source;

[0066] S2, adding 0.04 mol of acetylacetone solution to the n-propanol solution of the metal source, stirring evenly, to obtain a polymer solution of the metal source;

[0067] S3, adding 0.02 mol of phenolic resin to the polymer solution of the metal source, stirring evenly, and then adding 0.2 mol of tetrahydroxydiborane, stirring evenly, to obtain a precursor solution;

[0068] S4, the precursor solution was solidified at 160 ° C, and after grinding, the precursor powder was obtained. The precursor powder was heated to 2000 ° C at a heating rate of 6 ° C / min, and then kept at 2000 ° C for 1 h. The protective atmosphere was argon gas. After cooling to room temperature, (Ta 0.25 Nb 0.25 Zr 0.25 Ti 0.25 )B2 high entropy ceramic powder, its XRD spectrum is attached Figure 5 .

[0069] Depend on Figure 5 It can be seen that the (Ta 0.25 Nb 0.25 Zr 0.25 Ti 0.25 )The diffraction peak of B2 high entropy ceramic powder is sharp and strong, indicating that the degree of solid solution formation is better.

[0070] Example 6

[0071] S1, weigh 0.015mol TaCl5, 0.015mol NbCl5, 0.015mol C 12 H 28 O4Zr, 0.015molC 16 H 36 O4Ti is dissolved in a n-propanol solution to obtain a n-propanol solution of a metal source;

[0072] S2, adding 0.06 mol of acetylacetone solution to the n-propanol solution of the metal source, stirring evenly, to obtain a polymer solution of the metal source;

[0073] S3, adding 0.015 mol of phenolic resin to the polymer solution of the metal source, stirring evenly, and then adding 0.36 mol of tetrahydroxydiborane, stirring evenly, to obtain a precursor solution;

[0074] S4, the precursor solution was solidified at a temperature of 180°C, and after grinding, a precursor powder was obtained; the precursor powder was heated to 2000°C at a heating rate of 5°C / min, and then kept at 2000°C for 12 hours, with an argon protective atmosphere, and cooled to room temperature to obtain (Ta 0.25 Nb 0.25 Zr 0.25 Ti 0.25 )B2 high entropy ceramic powder, its XRD spectrum is attached Figure 5 .

[0075] Example 7

[0076] S1, weigh 0.015mol TaCl5, 0.015mol NbCl5, 0.015mol C 12 H 28 O4Zr, 0.015molC 16 H 36 O4Ti is dissolved in a n-propanol solution to obtain a n-propanol solution of a metal source;

[0077] S2, adding 0.06 mol of acetylacetone solution to the n-propanol solution of the metal source, stirring evenly, to obtain a polymer solution of the metal source;

[0078] S3, add 0.02 mol of phenolic resin to the polymer solution of the metal source, stir evenly, then add 0.3 mol of tetrahydroxydiborane, stir evenly, to obtain a precursor solution; heat the precursor powder to 2200°C at a heating rate of 6°C / min, then keep it at 2200°C for 1.5h, with argon as the protective atmosphere, and cool it to room temperature to obtain (Ta 0.25 Nb 0.25 Zr 0.25 Ti 0.25 )B2 high entropy ceramic powder, its XRD spectrum is attached Figure 6 .

[0079] Depend on Figure 6 It can be seen that the (Ta 0.25 Nb 0.25 Zr 0.25 Ti 0.25 )The diffraction peak of B2 high entropy ceramic powder is sharp and strong, indicating that the degree of solid solution formation is better.

[0080] Example 8

[0081] S1. Weigh 0.02mol TaCl5, 0.02mol NbCl5, 0.02mol C 12 H 28 O4Zr, 0.02mol C 16 H 36 O4Ti is dissolved in a n-propanol solution to obtain a n-propanol solution of a metal source;

[0082] S2. 0.08 mol of acetylacetone solution was added to the n-propanol solution of the metal source and stirred to obtain a polymer solution of the metal source;

[0083] S3. 0.025 mol of phenolic resin was added to the polymer solution of the metal source, and after stirring, 0.4 mol of tetrahydroxydiborane was added and stirred to obtain a precursor solution;

[0084] S4, the precursor solution was solidified at a temperature of 200°C, and after grinding, a precursor powder was obtained; the precursor powder was heated to 2200°C at a heating rate of 5°C / min, and then kept at 2200°C for 2h, with an argon atmosphere as the protective atmosphere, and cooled to room temperature to obtain (Ta 0.25 Nb 0.25 Zr 0.25 Ti 0.25 )B2 high entropy ceramic powder, its XRD spectrum is attached Figure 6 .

[0085] Comparative Example 1

[0086] This comparative example uses the boron thermal reduction method to synthesize high entropy boride powders, selects ZrO2, Ta2O5, Nb2O5, and TiO2 powders as raw materials, selects boron powder as the boron source, mixes them evenly through ball milling, dries the milled material, and heats it in a vacuum atmosphere furnace. The atmosphere furnace is heated to 1700℃ at a heating rate of 8℃ / min in an argon atmosphere and kept warm for 1h. After the insulation is completed, it is naturally cooled to room temperature to obtain high entropy boride ceramic powders.

[0087] Comparative Example 2

[0088] This comparative example is substantially the same as Example 5, except that n-propanol is replaced by ethanol.

[0089] Comparative Example 3

[0090] In this control example, the boron / carbon thermal reduction method is used to synthesize high entropy boride powder. ZrO2, Ta2O5, Nb2O5, and TiO2 powders are selected as raw materials and planetary ball milled with B4C powder for 10 hours. The powder obtained by ball milling is dried and placed in a vacuum sintering furnace and heated to 1600°C and kept warm for 1 hour. After the insulation period, it is cooled to room temperature and ground to obtain high entropy boride ceramic powder.

[0091] Comparative Example 4

[0092] In this control example, a sol-gel route is used to synthesize high entropy boride ceramic powder. Transition metal chloride is selected as a raw material, boric acid is used as a boron source, sorbitol, citric acid and ethylene glycol are added to the above solution in sequence, and then the solution is heated to 75°C and stirred to obtain a wet gel, which is dried to obtain a dry gel, which is then calcined at 1650°C for 3 hours in a tubular furnace under an argon atmosphere to synthesize a high entropy boride ceramic powder.

[0093] The present invention uses a nitrogen oxygen analyzer to measure the oxygen content in the high entropy ceramic powder obtained in the above embodiment and the control example. The test results are shown in Table 1.

[0094] Table 1 Test results

[0095] Serial number Oxygen content% Example 1 1.05 Example 2 1.05 Example 3 0.77 Example 4 0.77 Example 5 0.65 Example 6 0.65 Example 7 0.79 Example 8 0.87 Comparative Example 1 2.06 Comparative Example 2 — Comparative Example 3 1.56 Comparative Example 4 1.49

[0096] It can be seen from Table 1 that the high entropy ceramic powder prepared by the present invention has the advantages of high purity and low oxygen content compared with the control example.

[0097] Among them, in Control Example 1, the residual B2O3 by-product of the synthesis reaction is the main reason why the high entropy ceramic powder has a higher oxygen content.

[0098] In Control Example 2, ethanol was used to dissolve the salt solution of four metal sources. This may be because ethanol is volatile and cannot form relatively low-activity metal alkoxides with M-Cl bonds (M = transition metal element), resulting in the inability to form a polymer with multiple transition metal elements, which in turn leads to the inability to prepare a high-entropy boride ceramic precursor.

[0099] In control examples 3-4, the ball milling process introduced oxygen impurities and residual reaction by-product B2O3 into the powder, resulting in a high oxygen content in the obtained high entropy ceramic powder.

[0100] In summary, the preparation method of the present invention can greatly improve the uniformity of each element at the molecular scale, thereby reducing the oxygen content of the high-entropy ceramic powder and improving the purity of the product under the premise of lowering the preparation temperature. The oxygen content of the prepared high-entropy ceramic powder is as low as 0.65%, which has the advantages of high purity and low oxygen content.

[0101] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing high entropy ceramic powder, characterized in that: The following steps are involved: S1, dissolving the metal source in n-propanol, mixing evenly, to obtain an n-propanol solution of the metal source; S2, adding acetylacetone to the n-propanol solution of the metal source, mixing evenly, to obtain a polymer solution of the metal source; S3, sequentially adding a carbon source and a boron source to the polymer solution of the metal source, mixing them evenly, to obtain a precursor solution; S4, the precursor solution is solidified and heat-treated in sequence to obtain a high entropy ceramic powder; Among them, the molecular formula of the high entropy ceramic powder is MB2, wherein M is four metal elements of Ta, Nb, Zr and Ti.

2. The preparation method according to claim 1, characterized in that: The Ta source is TaCl5, the Nb source is NbCl5, and the Zr source is ZrCl4, C 12 H 28 O4Zr or ZrOCl2·8H2O, Ti source is TiCl4, C 16 H 36 O4Ti or C8H 20 Any one of O4Ti, and the molar ratio of the four metal elements of Ta source, Nb source, Zr source and Ti source is 1:1:1:

1.

3. The preparation method according to claim 1, characterized in that: The carbon source is phenolic resin.

4. The preparation method according to claim 1, characterized in that: The boron source is tetrahydroxydiborane.

5. The preparation method according to claim 1, characterized in that: The total molar number of the acetylacetone is equal to that of all metal elements.

6. The preparation method according to claim 1, characterized in that: The total molar ratio of the boron source to all metal elements is (1-5):

1.

7. The preparation method according to claim 1, characterized in that: During the curing, the temperature is controlled to be 80-200°C.

8. The preparation method according to claim 1, characterized in that: During the heat treatment, the temperature is raised to 1500-2200° C. at a heating rate of 3-9° C. / min, and then maintained at 1500-2200° C. for 0.5-2 h.

9. A high entropy ceramic powder, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8, the molecular formula of the high entropy ceramic powder is (Ta 0.25 Nb 0.25 Zr 0.25 Ti 0.25 )B2.

10. Use of the high entropy ceramic powder prepared by the preparation method according to any one of claims 1 to 8 or the high entropy ceramic powder according to claim 9, characterized in that: The high entropy ceramic powder is used in the fields of aerospace or energy.

Citation Information

Patent Citations

  • Boride high-entropy ceramic precursor, high-entropy ceramic and preparation method

    CN114988881A

  • High-entropy ceramic-based composite material and preparation method thereof

    CN115784746A

  • Composite carbide ceramic powder material as well as preparation method and application thereof

    CN116514553A

  • Method for preparing superfine single-phase boride and high-entropy boride powder at low temperature

    CN118026694A

  • High-entropy carbide ceramic and rare earth-containing high-entropy carbide ceramic, fibers and precursors thereof, and methods for preparing the same

    US20230088418A1

Cited By

  • Ultrahigh-temperature ceramic precursor, preparation method thereof, modified high-performance inorganic fiber and application

    CN120737362A